Bảo tồn các giống vật nuôi có vốn gen quý của Việt Nam - Hoàng, Văn Triệu (2011)
Tác giả: Hoàng Văn Triệu, PGS-TS; Võ Văn Sự; Nguyễn Như Cương; Lê Thị Thuý; Trần Văn Do; Vi Văn Vân -- Từ khóa: Bảo tồn; Lưu giữ; Gen; Giống vật nuôi